ANALISIS KERAPATAN VEGETASI DAN PENGARUHNYA TERHADAP LAND SURFACE TEMPERATURE DI KABUPATEN PASAMAN BARAT - Ririn Eriska; Paus Iskarni (JURUSAN GEOGRAFI FIS UNP, 2021)
Purpose of the research is : 1) To find out the vegetation density in 2008, 2014, and 2020 at West Pasaman Regency, 2) To find out the influence and relationship of vegetation density in 2008, 2014, and 2020 at West Pasaman Regency. The method that used to see the vegetation density is NDVI ( normalized difference vegetation index ) and to see surface of temperature is LST ( land surface temperature ). The result of this research is : 1) within 12 years the density of very dense vegetation increased by 76723 Ha. 2) LST analysis shows that the surface temperature in 2008 was 10,92-37,23°C, in 2014 surface temperature 13,85-35,31°C, and in 2020 ground surface temperature 7,57-34,20°C, 3) The results of the regression analysis shows that the vegetation density was closely related to surface temperature with R square in 2008 is 0.96 with an influence level 96%, in 2014 is 0.92 with an influence level 92% and in 2020 is 0,95 with an influence level 95%.